The influence of TiO2 nanoparticles and poliacrilonitrile fibers on the rheological behavior and hardened properties of mortars. (30th January 2015) - Senff, L.; Modolo, R.C.E.; Tobaldi, D.M.; Ascenção, G.; Hotza, D.; Ferreira, V.M.; Labrincha, J.A.
Highlights: DoE was used to formulate mortars with nano-TiO2 and poliacrilonitrile fibers. The use of rheometry can play a relevant role on the final properties. Mortars with similar initial yield stress and workability diverged over time. Rheology was governed by nano-TiO2 . Mechanical properties were mainly influenced by poliacrilonitrile fibers. Abstract: This experimental research evaluates the individual and combined influence of poliacrilonitrile (PAN) fibers and nanoTiO2 (nT) particles on the fresh and hardened properties of mortars up to 28 days. Samples with 0–0.125 wt% PAN, 0–1.0 wt% nT and 0.83–0.87 W / B were prepared. Samples with similar workability showed distinct rheological behavior along time and the yield stress was the best rheological parameter to represent such variations. The very high specific surface area and wettability of nT was dominant over the one induced by PAN fibers and severely limited the rheological behavior maintenance up to 0.050PAN + 1.00nT sample. The physical properties (apparent density, water absorption, apparent porosity) indicate that PAN is dependent on the correct correlation with nT particles. In addition, the optimal concentration of PAN is about 0.05 wt% to the flexural and compressive strength, while the most active NO x degradation reached ∼77% to those containing 1 wt% nT, regardless the concentration of PAN.